Answer:
C. 3
Step-by-step explanation:
The constant of proportionality is the slope (or rate of change) of the graph.
To find the equation of the graph;
Take points (1,3) and (3,9)
The slope (m) = change in y ÷ change in x
m = ![\frac{9 - 3}{3 - 1} = \frac{6}{2} = 3](https://tex.z-dn.net/?f=%5Cfrac%7B9%20-%203%7D%7B3%20-%201%7D%20%3D%20%5Cfrac%7B6%7D%7B2%7D%20%3D%203)
Taking another point (x,y) on the graph;
m = ![\frac{y - 3}{x - 1} = 3](https://tex.z-dn.net/?f=%5Cfrac%7By%20-%203%7D%7Bx%20-%201%7D%20%3D%203)
y - 3 = 3x - 3
y = 3x + 0
y = 3x
This can be expressed as;
y ∝ 3x
Which means that as y rises, x rises too but 3 remains the same. The value 3 is the constant of proportionality in this relationship.